Menguji Konsep Serta Menemukan Konfusi: Materi Torsi dan Rotasi pada SMA Negeri 1 Kota Serang - Niken Apriyanti; Nathanael Alexander Silalahi; Tresna Galih Sukma Suryana (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the misconceptions in students in SMAN 1 Kota Serang on the material of Torque and Rotation. The research tested was a two-tier based question, consisting of 13 multiple choice questions with five answer options and one supporting reason for each answer. Data collection was carried out through Google Form media and distributed to 36 students of class XI IPA 9. The data obtained were students understood 13.9%, partially understood 11.1%, misunderstanding 22.2%, specific misunderstanding 33.3%, and did not understand 19.5%. This test is based on the result was tested there were students' misconceptions, namely the moment of force 5.55%, the relationship between force and moment of force 25%, the position of force to the axis 75%, the equation of rotation and GLBB 41.66%, Linear kinetic energy from frequency and radius 69.44%, The relationship between centripetal acceleration and radius 80.55%, and the kinetic energy of rolling objects 63.88%. The results of this test are analyzed into which parts of the students experience misconceptions, with these findings expected to be used as a basis for designing targeted learning interventions.